2011
DOI: 10.1007/s10846-011-9612-2
|View full text |Cite
|
Sign up to set email alerts
|

Human Detection and Identification by Robots Using Thermal and Visual Information in Domestic Environments

Abstract: In this paper a robust system for enabling robots to detect and identify humans in domestic environments is proposed. Robust human detection is achieved through the use of thermal and visual information sources that are integrated to detect human-candidate objects, which are further processed in order to verify the presence of humans and their identity using face information in the thermal and visual spectrums. Face detection is used to verify the presence of humans, and face recognition to identify them. Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…As a result, an attractive solution is the combination of both optical and thermal images in many sensing and surveillance scenarios as the complementary nature of both modalities can be exploited and the individual drawbacks largely compensated (e.g. [27,3,9,13,7]). …”
Section: Introductionmentioning
confidence: 99%
“…As a result, an attractive solution is the combination of both optical and thermal images in many sensing and surveillance scenarios as the complementary nature of both modalities can be exploited and the individual drawbacks largely compensated (e.g. [27,3,9,13,7]). …”
Section: Introductionmentioning
confidence: 99%
“…One potential approach to detect humans is to endow robots of specific sensors such as RFID or thermal sensors (Correa et al, 2012). In spite of high performances, this solution requires ad hoc hardware, usually not available in common robotics platform, limiting the range of possible scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…After comparing several methods, they concluded that the best-performing method for HRI applications, in terms of recognition rate and real-time operation, is LBP-histograms using histogram intersection or Euclidean distance as similarity measures in the visual and thermal spectra. Based on similar ideas, another work [37] proposed the robust detection of humans through thermal and visual information sources that are integrated to detect human-candidate objects, which are further processed to verify the presence of humans and their identity using face information in the thermal and visual spectra. Face detection is used to verify the presence of humans, and face recognition is used to identify them.…”
Section: Person Recognition and Trackingmentioning
confidence: 99%